2019
DOI: 10.1016/j.cgh.2018.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Safety of Vedolizumab in Patients With Inflammatory Bowel Diseases

Abstract: BACKGROUND & AIMS: There are few real-world data on the safety of vedolizumab for treatment of Crohn's disease (CD) or ulcerative colitis (UC). We quantified rates and identified factors significantly associated with infectious and non-infectious adverse events in clinical practice. METHODS: We performed a retrospective review of data from a multicenter consortium database (from May 2014 through June 2017). Infectious and non-infectious adverse events were defined as those requiring antibiotics, hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 18 publications
7
43
1
4
Order By: Relevance
“…Importantly, there were no cases of PML, a known toxicity with nonspecific a4 integrin inhibition [28]. In a recent retrospective cohort study, the number of concomitant immunosuppressive agents (corticosteroids or immunomodulators; OR, 1.72 per agent) used was associated with infections [29]. This study also reported that gastrointestinal infections were observed in the inflammatory bowel disease patients who were treated with vedolizumab (2.4 per 100 patient years of exposure).…”
Section: Discussionmentioning
confidence: 86%
“…Importantly, there were no cases of PML, a known toxicity with nonspecific a4 integrin inhibition [28]. In a recent retrospective cohort study, the number of concomitant immunosuppressive agents (corticosteroids or immunomodulators; OR, 1.72 per agent) used was associated with infections [29]. This study also reported that gastrointestinal infections were observed in the inflammatory bowel disease patients who were treated with vedolizumab (2.4 per 100 patient years of exposure).…”
Section: Discussionmentioning
confidence: 86%
“…The ideal approach to selecting dual biologic regimens remains to be determined. Vedolizumab or ustekinumab may be ideal adjunct therapies in DBT regimens due to their favourable safety profile 12,13,21,22 . For this reason, most patients in our study received vedolizumab, and the most frequently used pairing was with ustekinumab.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, newer approved biologic agents for Crohn's disease such as vedolizumab and ustekinumab have not yet demonstrated these risks. Vedolizumab targets the α4β7 integrin receptor to block lymphocyte homing to the intestinal mucosa, and has demonstrated a favourable safety profile in clinical trial 12 and real‐world 13 settings. Ustekinumab inhibits the common p40 subunit of IL‐12 and −23 and is safe and effective in Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, no differences were noted with any concomitant therapy in Israeli cohorts or the VICTORY or Cross Penine cohorts (3,(17)(18)(19). Regardless of these results, it is important to remember that the appeal of the relative safety for VDZ is decreased with combination therapy with corticosteroids and/or immunomodulators (20), and there also does not appear to be the same risk of immunogenicity or benefit of increased trough levels with concomitant immunomodulators for VDZ (21,22) (Table 2).…”
Section: Concomitant Immunosuppressive Therapymentioning
confidence: 99%